Kaifiyah Sujud Sahwi dan Sujud Tilawah - Amalia Muflihah Rahmasari; Hafidzhotul Mumtazah; Mohammad Faiq Akmal; Sarah Azka Fiddaroin (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Prostration of forgetfulness (sujud sahwi) and prostration of recitation (sujud tilawah) represent two manifestations of additional prostrations in Islamic worship that are crucial for maintaining the perfection of prayer (shalat) and the deep comprehension of the Qur'an. This research comprehensively analyzes the kaifiyah (procedures), requirements, pillars (rukn), sharia evidences (dalil syar'i), madhab differences, and their spiritual wisdoms. Utilizing a normative juridical method with an in-depth literature analysis of primary sources (the Qur'an, Sunnah, and text manuals/ kitab mutun of the Shafi'i school), the results demonstrate that sujud sahwi effectively corrects inadvertent errors, such as additions (ziyadah) or omissions (nisyan) in prayer, while sujud tilawah is required when a verse of prostration (ayat sajdah, consisting of 15 verses) is recited or heard. The discussion encompasses practical examples and comparative analyses. The conclusion emphasizes the urgency of teaching these practices amidst the rising prevalence of modern worship errors, along with recommendations for Islamic boarding school (pesantren) curricula.